2013
DOI: 10.1128/cvi.00268-13
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Binding Domain of Botulinum Neurotoxin Serotype A (BoNT/A) Inhibits BoNT/A and BoNT/E Intoxications In Vivo

Abstract: The receptor binding domain of botulinum neurotoxin (BoNT), also designated the C terminus of the heavy chain (H C ), is a promising vaccine candidate against botulism. In this study, a highly efficient expression system for the protein was developed in Escherichia coli, which provided yields that were 1 order of magnitude higher than those reported to date (350 mg H C per liter). The product was highly immunogenic, protecting mice from a challenge with 10 5 50% lethal dose (LD 50 ) after a single vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…It is very hard to compare protective activity of anti-H N 519–593 with that of anti-H C Abs. Those studies 10 29 30 31 32 33 measured toxin challenge doses in LD 50 units, whereas the present work used toxin doses in 1.05 × LD 100 units. We strongly believe that a construct comprising the two domains would provide a more efficient vaccine than either alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is very hard to compare protective activity of anti-H N 519–593 with that of anti-H C Abs. Those studies 10 29 30 31 32 33 measured toxin challenge doses in LD 50 units, whereas the present work used toxin doses in 1.05 × LD 100 units. We strongly believe that a construct comprising the two domains would provide a more efficient vaccine than either alone.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this work shows the potential of recombinant R domains as toxoids and the importance of conformational epitopes in generating a protective antitoxin immune response. It has been confirmed recently by other teams with successful immunization of mice with R domains of botulinum neurotoxins [20,21].…”
Section: Toxoids Based On Receptor-binding Domains Of Toxinsmentioning
confidence: 63%
“…showed that the recombinant HCR of BoNT/A protected mice from BoNT/A intoxication. 22 In fact, the most advanced vaccine candidate for botulinum is a recombinant HCR subunit that is currently undergoing clinical trials. Although recombinant HCRs can protect animals, they can also enter neurons that are similar to BoNT/A via synaptic vesicle protein 2.…”
Section: Discussionmentioning
confidence: 99%